Large-scale resource state monitoring strategy in network function virtualization environment - Meisheng HAI; Peng YI; Yiming JIANG; Jichao XIE (网络与信息安全学报)
In order to improve the utilization of the infrastructure resource and efficiently deploy the service function chain dynamically in network function virtualization,the orchestration management domain needs to monitor the network resources and virtual network function status in real time,but real-time monitoring will bring large communication overhead.An intelligent distributed monitoring strategy with minimal network communication overhead was proposed.The improved label propagation algorithm intelligently subnets and selects agent monitoring nodes to achieve efficient monitoring of resource and virtual function status and minimize monitoring information communication overhead.The simulation results show that the monitoring strategy proposed reduces the monitoring information communication overhead in the network by about 13%.